2013
DOI: 10.1186/1471-2431-13-180
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with in-office influenza vaccination by U.S. pediatric providers

Abstract: BackgroundIn the United States, influenza vaccination is recommended for all children 6 months and older; however, vaccination rates are below target levels. A broad sample of U.S. pediatric offices was assessed to determine factors that influence in-office influenza vaccination rates.MethodsOffices (N = 174) were recruited to participate in an observational study over three influenza seasons (2008–2009, 2009–2010, 2010–2011). Only data from the first year of an office’s participation in the study were used. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For HCPs, the results are rather inconclusive, with one study reporting increased size as a barrier (1/117 [ 343 ]) and 2 studies reporting it as a promoter (2/117 [ 438 , 439 ]). For patients and residents, an increased size of care facility was consistently noted as a barrier (Elderly 1/62 [ 302 ]; Public 2/191 [ 440 , 441 ]).…”
Section: Resultsmentioning
confidence: 99%
“…For HCPs, the results are rather inconclusive, with one study reporting increased size as a barrier (1/117 [ 343 ]) and 2 studies reporting it as a promoter (2/117 [ 438 , 439 ]). For patients and residents, an increased size of care facility was consistently noted as a barrier (Elderly 1/62 [ 302 ]; Public 2/191 [ 440 , 441 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical decision support functions in IIS and other electronic health systems can also make recommendations to providers on patients’ vaccine needs. In addition, patient reminders can also be considered as they are positively associated with in-office influenza vaccination [17]. Lastly, the lags observed in the timing of dose administration among children who required two doses and received only one dose, compared with the timing of first dose administration among children who required and received two doses, might reflect a subset of the population with differing access to vaccination services, knowledge of vaccination recommendations, or motivation to receive influenza vaccination for their children, but the reasons for this delay would require further investigation beyond the scope of this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Because flu vaccine is given annually, and not throughout the year, it requires specific strategies that differ from other vaccinations. Offering flu vaccination for longer in the season leads to higher immunization rates, 61 as does having weekend/evening clinics for vaccination. 62 One study showed improved rates for infants and children with asthma by making appointments for "flu clinics" year round.…”
Section: T a G G E D H 1 Multi-faceted Interventionst A G G E D E N Dmentioning
confidence: 99%